FAMILY RITUALS AND PROBLEMATIC SMARTPHONE USE IN ADOLESCENTS - Maulida, Isni Sania; Anindhita, Vidya; Abidin, Fitri Ariyanti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Family factors have been identified as potential protective or risk factors for problematic smartphone use in adolescents, yet studies on family rituals as one of the important family factors are scarce. Therefore, this study investigates the relationship between family rituals and problematic smartphone use in adolescents. Family rituals were measured using the Family Ritual Questionnaire (FRQ), and problematic smartphone use was measured using the Mobile Phone Problematic Use Scale (MPPUS). Both measurements were validated in the Indonesian version. Using a cross-sectional approach, we applied a convenience sampling method. Two hundred and twelve adolescents aged 12-18 (girls= 113, boys= 98; Mean age= 14.56, SD= 1.41) participated in this study. The data was analyzed using Spearman’s rho correlation analysis. The results show no significant correlation between family rituals and problematic smartphone use in adolescents (r = 0.01; p > 0.05). Further investigation involving family communication as a mediating variable is strongly recommended.